Development and psychometric evaluation of the basic electrocardiogram interpretation self-efficacy scale - Hernández-Padilla, José Manuel (2016)
Purpose: Research suggests that nurses and nursing students lack competence in basic electrocardiogram (ECG) interpretation. Self-efficacy is considered to be paramount in the development of one's competence. The aim of this study was to develop and psychometrically evaluate a scale to assess self-efficacy of nursing students in basic ECG interpretation. Materials and methods: Observational cross-sectional study with a convenience sample of 293 nursing students. The basic ECG interpretation self-efficacy scale (ECG-SES) was developed and psychometrically tested in terms of reliability (internal consistency and temporal stability) and validity (content, criterion and construct). The ECG-SES’ internal consistency was explored by calculating the Cronbach's alpha coefficient (α); its temporal stability was investigated by calculating the Pearson correlation coefficient (r) between the participants’ results on a test–retest separated by a 4-week interval. The content validity index of the items (I-CVI) and the scale (S-CVI) was calculated based on the reviews of a panel of 16 experts. Criterion validity was explored by correlating the participants’ results on the ECG-SES with their results on the New General Self-Efficacy Scale (NGSE). 1 Construct validity was investigated by performing Principal Component Analysis (PCA) and known-group analysis. Results: The excellent reliability of the ECG-SES was evidenced by its internal consistency (α = 0.98) and its temporal stability at the 4-week re-test (r = 0.81; p < 0.01). The ECG-SES’ content validity was also excellent (all items’ I-CVI = 0.94–1; S-CVI = 0.99). A strong, significant correlation between the NGSE and the ECG-SES (r = 0.70; p < 0.01) showed its criterion validity. Corroborating the ECG-SES’ construct validity, PCA revealed that all its items loaded on a single factor that explained 74.6% of the total variance found. Furthermore, known-groups analysis showed the ECG-SES’ ability to detect expected differences in self-efficacy between groups with different training experiences (p < 0.01). Conclusion: The ECG-SES showed excellent psychometric properties for measuring the self-efficacy of nursing students in basic ECG interpretation.